Noise exposure and stress responses in textile industry - Tsong, Jia Yan (2015)
Textile Industries are developing rapidly to meet the necessities of human beings by supplying the basic needs of cloth for day to day needs. With the rapid development, there are several issues that occurring in the textile industry. Noise pollution is the most often severely exposed by the workers due to the machines used in the operations and may developed stress consequence among the workers. This study was conducted in a textile industry with fifty respondents to assess the relationship between noise exposure and its effect towards stress among highly exposed and low exposed workers. Environmental and personal noise level was measured using Sound Level Meter and Personal Noise Dosimeter respectively. Stress responses were obtained from the Depression Anxiety and Stress Scale (DASS) questionnaire. It was found that there is a significant relationship (r = 0 .0864**, p<0.05) between personal and environmental noise levels. Besides that, there is also a significant difference (t = -6.045, p<0.05) on individual noise level between exposed and low exposed groups. However, there is no significant relationship between noise level and stress responses among the workers because of the effective periodically hearing conservation practice that applied in the textile industry.